Nitric oxide and abscisic acid regulate osmoprotective and antioxidative mechanisms related to water stress tolerance of grapevines - Pontin, Mariela Ana; Murcia, Mauro German; Bottini, Ambrosio Rubén; Fontana, Ariel; Bolcato, Leonardo; Piccoli, Patricia Noemí (Wiley, 2021)
Background and Aims: Exogenously applied nitric oxide (NO) and abscisic acid (ABA) are known to improve the tolerance of plants to abiotic stress. The effects of NO and ABA applications on physiological and metabolic responses associated with vine protection against water stress were analysed. Methods and Results: The responses to the NO donor sodium nitroprusside (hereinafter referred to as NO treatment) and ABA were assessed on metabolic profiling, the activity of antioxidant enzymes, and physiological parameters in leaves of water‐stressed Malbec vines. Application of NO and ABA partially closed stomata, thus increasing water potential and reducing vine growth. As well, NO and ABA increased guaiacol peroxidase activity and the concentration of specific sugars and anthocyanins in leaves, whereas the accumulation of amino acids was reduced, in turn associated with less protein degradation. Differential responses triggered by NO in stimulating ascorbate peroxidase activity and in incrementing tricarboxylic acid cycle intermediates and terpenes that stabilise membranes, suggest differential mechanisms for NO and ABA in counteracting water stress effects in leaves of grapevines. Conclusions: Nitric oxide and ABA differentially regulate osmoprotective and antioxidative mechanisms related to water stress tolerance in grapevines.